Modelling of flow modes in membrane dispensers of automatic packaging machines - Diachenko, Ivan; Tokarchuk, Serhii (My University, 2025)
The efficiency of bulk food packaging depends on the design and flow characteristics of the dosing device. Diaphragm dosing devices that do not have traditional moving parts reduce energy consumption, reduce wear and tear, and increase reliability. To ensure dosing accuracy, it is important to model flow dynamics taking into account the properties of different products.

Ефективність пакування сипучих харчових продуктів залежить від конструкції та характеристик потоку дозуючого пристрою. Мембранні дозатори, які не мають традиційних рухомих частин, знижують енергоспоживання, зменшують знос і підвищують надійність. Для забезпечення точності дозування важливо моделювати динаміку потоку з урахуванням властивостей різних продуктів
Keywords: кафедра мехатроніки та пакувальної техніки; modelling; flow modes; membrane dispensers; automatic packaging machines; моделювання; режими течії; мембранні дозатори; пакувальні автомати